Social anxiety and emoji use: gender differences and the role of loneliness in digital communication among college students - Bendl, Alexis M.; Cunningham, Ronan M.; Hill, Lauren; Jarcho, Johanna M. (Frontiers in Psychology, 2025)
Emojis are one of the fastest growing forms of digital communication. However, sending texts can provoke distress. This may be particularly true for the 40% of emerging adults with clinically significant symptoms of social anxiety who often suffer from loneliness and altered communication styles. We hypothesize that to mitigate distress, higher levels of social anxiety and loneliness may be associated with greater emoji use when sending texts that could be interpreted negatively. We also hypothesize the relation would be especially pronounced in females given higher rates of social anxiety and emoji use in general. College students (N = 191, 64% female, 18–24 years of age) read a series of vignettes with ambiguous texts and were asked to imagine sending them to a friend. They were instructed to convey positive meaning for half of the texts and negative meaning for the other half. Participants replied with a pre-written response and were given the option to send the response as is or add an emoji expressing a facial expression ranging from happy to displeased. Social anxiety and loneliness were assessed using established self-report scales. Multiple linear regression [R2 = 0.072, F(3,107) = 3.859, p = 0.012] demonstrated that women with high levels of both social anxiety and loneliness used emojis more frequently, and that this varied depending on valence. Specifically, women with high social anxiety used emojis more frequently when conveying positively valanced messages (β = 0.338, p = 0.003). No relations emerged between social anxiety, loneliness and emoji use in men [R2 = 0.044, F(3,52) = 1.844, p = 0.151]. Although the effect sizes are small, these findings may inform the design of future studies on mental health and digital communication, increase understanding about gender differences in online communication style, and provide preliminary insights for the development of digital interventions that identify young adults who may most benefit from clinical engagement.